Investigating the Relationship between Technology Acceptance Factors and Behavioural Intention to Use of Online Food Delivery Applications in Sarawak - Nur Suriayanti, Gadiman; Norizan, Jaafar; Janifer, Lunyai (HRMARS, 2023)
The current study investigated the relationships between technology acceptance factors and behavioural intention to use of online food delivery applications in Sarawak. The framework of this research was drawn from the perspective of the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model with two additional constructs, namely trust and risk. The study was based on a sample gathered from users of online food delivery applications in Sarawak. Data were collected using a self-administered online questionnaire. Of the 411 returned questionnaires, 400 questionnaires were valid for analysis. IBM-SPSS Amos 24.0 procedures were utilised to analyse the data and test the hypotheses. The findings of the study lead to the conclusion that the relationship between 6 constructs (effort expectancy, facilitating condition, hedonic motivation,trust and risk) and behavioural intention to use online food delivery applications are significant. Meanwhile, there are not significant relationship between 4 constructs (performance expectancy, social influence, price value and habit) and behavioural intention to use online food delivery applications. The significance of the findings enable to highlight the important factors for promoting online food delivery applications among users in aforesaid context.